2000
DOI: 10.1352/0047-6765(2000)038<0385:hofcti>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

How Organizational Factors Contribute to Innovations in Service Delivery

Abstract: Twelve staff members from three community centers providing services to people with mental retardation were interviewed about the implementation of a new approach to service delivery that utilized Essential Lifestyle Planning. Findings indicate that although the innovation proposed and the technical assistance provided were quite similar, the outcomes varied greatly across the three sites. By highlighting the importance of organizational factors, such as timing and agency supports, these findings provide direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Regarding the internal factors facilitating or inhibiting innovation, the research results indicated that strong leadership, shared and clear objectives, task orientation, participative safety, reflective team practices, active internal marketing, correct timing, motivation and participation of personnel, lack of stress, and sufficient resources (financial, instrumental, and personal) all seem to be positively related to innovation in healthcare organizations (Becker et al, 2000;Castle, 2001;Cohen et al, 2004;Edmondson, Bohmer, & Pisano, 2001;Ericson, 2001;Evashwick & Ory, 2003;Felton, 2003;Länsisalmi & Kivimäki, 1999;West & Anderson, 1996). In studies of the structure and type of teams, no differences were found between single-disciplinary, multidisciplinary, management, and primary healthcare teams' climate profiles, that is, support for innovation and task orientation (Williams & Laugani, 1999).…”
Section: Summary Of Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding the internal factors facilitating or inhibiting innovation, the research results indicated that strong leadership, shared and clear objectives, task orientation, participative safety, reflective team practices, active internal marketing, correct timing, motivation and participation of personnel, lack of stress, and sufficient resources (financial, instrumental, and personal) all seem to be positively related to innovation in healthcare organizations (Becker et al, 2000;Castle, 2001;Cohen et al, 2004;Edmondson, Bohmer, & Pisano, 2001;Ericson, 2001;Evashwick & Ory, 2003;Felton, 2003;Länsisalmi & Kivimäki, 1999;West & Anderson, 1996). In studies of the structure and type of teams, no differences were found between single-disciplinary, multidisciplinary, management, and primary healthcare teams' climate profiles, that is, support for innovation and task orientation (Williams & Laugani, 1999).…”
Section: Summary Of Findingsmentioning
confidence: 98%
“…External factors that were found to have a positive relationship with the adoption of practice and service innovations were involvement, motivation, and support (in the form of training consultants and technical support) provided by key stakeholders in the organizational context (Becker, Dumas, Houser, & Seay, 2000;Cohen et al, 2004;Evashwick & Ory, 2003). Furthermore, active contacts with external parties were found to enhance the quantity of service innovations and the quantity of new technologies adopted by hospitals over time (Goes & Park, 1997).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…A keystone of the transformation of services for people with learning disabilities is that individuals with learning disabilities themselves are facilitated in identifying the outcomes that are meaningful to them and that services have the organisational structure to respond positively to these self-identified needs (Becker et al, 2000).…”
Section: Hearing the Voice Of People With Learning Disabilitiesmentioning
confidence: 99%